Очисне обладнання в содовому виробництві - Грубнік, Аліна Олегівна (Національний університет "Львівська політехніка", 2018)
Improvement of soda production until recently has been aimed at improving the technology and modernization of the equipment of the main production cycle. The creation of equipment for the protection of the environment was not given much attention. Gases and liquids were cleaned only from ammonia. And then to the limits, justified economically, and not sanitary norms
Keywords: содові підприємства; утилізація теплоти вторинних джерел; пил соди; діоксид вуглецю; аміак; очищення промислових газових викидів